2018
DOI: 10.3390/ijerph15091871
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Urinary Hydrogen Peroxide and 8-Hydroxy-2′-Deoxyguanosine Levels after a Forest Walk: A Pilot Study

Abstract: Some studies have shown that exposure to forests has positive effects on human health, although the mechanisms underlying the health benefits of a forest environment have not been elucidated yet. The current study was aimed at examining how the levels of urinary hydrogen peroxide (H2O2) and 8-hydroxy-2’deoxyguanosine (8-OHdG) change after a forest or urban walk in healthy subjects. Twenty-eight volunteers (19 men and 9 women) participated in the study. The forest walks were carried out in a forest in Okayama P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 28 publications
0
13
0
1
Order By: Relevance
“…A background range for 8-OHdG has been reported in different studies for healthy persons [11,[18][19][20]. However, these studies reported a wider range of values, making the identification of background cut-off values challenging.…”
Section: Descriptive Resultsmentioning
confidence: 99%
“…A background range for 8-OHdG has been reported in different studies for healthy persons [11,[18][19][20]. However, these studies reported a wider range of values, making the identification of background cut-off values challenging.…”
Section: Descriptive Resultsmentioning
confidence: 99%
“…Japanese scholars had the largest number of studies, publishing 13 papers [19, 20, 2225, 28, 31, 38, 40, 4244], accounting for 46% of the total number of included studies, followed by Chinese, South Korean, Taiwanese, and Polish scholars, publishing 6 papers [27, 32, 37, 39, 45, 46], 5 papers [21, 26, 29, 30, 34], 3 papers [33, 36, 41], and 1 paper [35], respectively, accounting for 21%, 18%, 11%, and 4% of the total number of included studies, respectively. Among them, there were 17 RCTs [20, 21, 2427, 3032, 35, 3740, 43, 45, 46], accounting for 61% of the total number of included studies, and 11 NRCTs [19, 22, 23, 28, 29, 33, 34, 36, 41, 42, 44], accounting for 39% of the total number of included studies. The participants were dominated by healthy people, with a total of 17 studies [20, 24, 26, 29, 31, 3338, 40, 4246], accounting for 61% of the total number of studies included, and mostly young people aged 18–30.…”
Section: Resultsmentioning
confidence: 99%
“…The urban walks took place in July–October, 2016–2019 in the downtown area of Okayama City ( Figure 1 b), which has a population of 720,066 and a total area of 789.95 km 2 ; the general traffic amount is less than 30,000 cars and trucks/24 h). Each walk comprised 2 h of slow walking with a gait velocity of less than 60 m/min [ 17 ], during which there were two to three short breaks as described by Wang et al [ 8 ]. The urban walks were carried out in 2016–2019, and the forest walks in Shinjo Village were added to the study in 2017–2019 ( Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…This imbalance may oxidatively damage DNA, proteins, and lipids [ 6 , 7 ]. Wang et al recently reported that urinary hydrogen peroxide (H 2 O 2 ) and 8-hydroxy-2′deoxyguanosine (8-OHdG) decreased after a forest walk but not after an urban walk [ 8 ]. Gibo et al also found a decreased serum malondialdehyde-modified low-density lipoprotein level (MDA-LDL) after a forest walk [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation